A case of long-term survival of primary malignant melanoma of the esophagus after surgery and a review of the literature - Zhao, Weigang; Guo, Xiang; Yang, Yi (Annals of Esophagus, 2019)
We here reported a case of primary malignant melanoma of the esophagus (PMME) which was performed surgery 8 years ago. The patient is still alive now. PMME is a very rare disease with very dreadful prognosis. The only way to definitely diagnosis is pathology while clinical symptoms or image examinations are useful for clinical staging. Surgery is standard, and only treatment that can offer the opportunity for long-term survival.